Language Problems in Thesis Writing, Medan State University, Anthropology Education Study Program - Syaqira, Nabila; Sitompul, Sherly Luisa; Sirait, Verawati Debora; Sihite, Firda; Siregar, Mustika Wati (CV. Rayyan Dwi Bharata, 2024)
a